Application of critical thinking technology in inclusive education in higher education (Journal of Educational Sciences, 2024)
The article considers an urgent problem that meets the needs of modern society - this is the method of applying critical thinking technology in inclusive education. Since the training of a competent specialist who qualitatively carries out inclusive education is the main task facing today's Higher School, which is engaged in the training of teaching staff. The authors describe the effectiveness of the use of critical thinking technology, its main methods and techniques in the development of the discipline "Inclusive Education", which is studied by all students of pedagogical specialties. The study presents the full content of the work carried out during the experimental work with 102 3rd-year students in the 2022-2023 academic year, systematically evaluates the results obtained on the basis of quantitative and qualitative methods. Based on the results of the research work, the possibilities of critical thinking technology are determined not only to master the educational material perfectly, but also to prepare a competent specialist who is able to flexibly adapt to today's rapidly changing society, with developed constructive thinking. The practical significance of the presented research work lies in the fact that in modern conditions of inclusive education, a group of effective methods that develop critical skills and a methodology for their presentation based on practical tasks are presented. The authors of the article analyzed in detail the theoretical literature, research work on the research topic, conducted a comprehensive analysis and formulated their conclusions. In particular, the methods and techniques used are described in detail, clearly revealing the three stages of critical thinking technology and defining in more detail the purpose of each of them. In addition, the definition has been clarified, which has the following content: "critical thinking is a positive thought process that allows you to make effective decisions in a certain situation based on knowledge, critical mentality and abilities.Keywords: Higher school, inclusive education, critical thinking technology, methods, critical thinking skills, argumentation, conclusion, effective solution.